Physical and mechanical properties of composite sago starch-oil edible film: article - Sylvester Silin, Joyce; Hamidon, Fariza (2018)
The depleting of the sources to produce the synthetic plastics that are used widely nowadays encourages the study of the packaging of bioplastics that is made from renewable sources. One of the bioplastic is the edible film that can be produced from the starch. Despite from having wide source, edible film is one of the alternatives to produce less waste in the world. The study is done to determine the mechanical and physical of the starch-oil composite edible film that was made from sago starch with incorporation of corn oil. The edible film was prepared using five gram of sago starch mixed with glycerol (0%, 8% and 16% v/w), corn oil (0%, 2%, 4% and 6% v/w). The films were characterized for thickness, water solubility and water vapor permeability (WVP), tensile strength (TS), percent elongation at break (EB). From the analysis, all of the characteristics were affected by the additives addition in the films. The thickness, water solubility, EB and WVP increased as the amount of glycerol increased, while the TS decreased.